ISLAMIC MORAL HABITUATION AND ITS EFFECT ON SELF-CONTROL AND MORAL RESPONSIBILITY AMONG PRIMARY STUDENTS - Nur Agus Salim; Rinovian Rais; Wati Karmila; Firmansyah Firmansyah; Putra, Purniadi (Nurul Jadid University, Paiton Probolinggo, East Java, 2026)
This study aimed to examine the effect of Islamic moral habituation programs on the development of self-control and moral responsibility among primary school students in Sambas Regency, West Kalimantan, Indonesia. This study employed a quantitative survey design. Data analysis used Structural Equation Modeling with Partial Least Squares (PLS-SEM) through SmartPLS 4. The study involved 200 students from Grades 4 and 5 across six Islamic primary schools. Three latent variables consisted of Islamic moral habituation (exogenous; 7 dimensions, 24 items), self-control (first endogenous; 5 dimensions, 20 items), and moral responsibility (second endogenous; 5 dimensions, 25 items). The structural model revealed that Islamic moral habituation had a significant positive effect on self-control (β = 0.469, t = 7.44, p < 0.001) and on moral responsibility (β = 0.542, t = 7.953, p < 0.001). The model demonstrated predictive relevance (Q² = 0.191 and 0.262) and explanatory power (R² = 0.22 and 0.294) with acceptable model fit (SRMR = 0.071). These findings confirmed that structured Islamic moral habituation served as a meaningful predictor of character development outcomes among primary school learners. The implication of this finding is that Islamic moral habits are effective in increasing students' self-control and responsibility, so they need to be implemented routinely by teachers as an important part of character education in Islamic primary schools.